ASSESSMENT OF THE REHABILITATION CULTURE DEVELOPMENT OF FAMILIES RAISING CHILDREN WITH DISABILITIES: PRAXIOLOGICAL ASPECT - Светлана Николаевна Викжанович; Ольга Юрьевна Синевич; Людмила Васильевна Тимошенко; Елена Александровна Чернявская; Наталья Николаевна Шерешик (The Publishing House Medicine and Enlightenment, 2022)
The article assesses the rehabilitation culture of families raising children with disabilities. The study of this problem was examined in the praxeological aspect by the methods of conversation with parents (64 people) and by observing the peculiarities of their interaction with their children. Among the praxeological skills, the following were assessed: psychohygienic, communication, psychological and pedagogical (special, necessary to meet the special educational needs of a child with developmental disabilities), as well as social advocacy skills. The article substantiates that the majority of parents do not have enough praxeological skills. Accordingly, the rehabilitation culture of families in which children with developmental disorders are brought up corresponds mainly to a low level.